The Use of Exercise Methods in Improving Student Learning Outcomes in the Material of Living and Practicing Religious Teachings That he Adheres to Class XI SOCIAL STUDIES-2 Students at SMAN 9 Ambon - Yuliana Kwaar; Agustinus Soumokil; Fatimah Sialana (IJRAEL: International Journal of Religion Education and Law, 2022)
This study aims to describe the improvement of learning outcomes in the material of living and practicing the religious teachings it adheres to by using the exercise method in class XI social studies-2 students at SMAN 9 AMBON. This type of research is classroom action research. The results of the study in the first cycle showed that student participation in learning was not good, in the first cycle there were 10 students or 40% of students who successfully met the KKM score, and in the results of the second cycle of research showed excellent learning participation, in cycle II there were 22 students or 80% of students who had successfully met the KKM score. The results of this study are that, the use of practice learning methods can improve student learning outcomes.